2017
DOI: 10.1007/s11010-017-3108-8
|View full text |Cite
|
Sign up to set email alerts
|

Aegle marmelos differentially affects hepatic markers of glycolysis, insulin signalling pathway, hypoxia, and inflammation in HepG2 cells grown in fructose versus glucose-rich environment

Abstract: Fructose consumption is responsible for the onset of insulin resistance (IR), and metabolic syndrome. It possesses no functional utility in body and its detrimental effects on hepatic metabolic milieu are beyond those produced by glucose. The need of the hour is to identify fructose-induced IR as an unique pathological state to be managed differentially. The effect of aqueous leaf extract of Aegle marmelos (AM) on hepatic markers of insulin resistance using HepG2 cells cultured in either fructose or glucose-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The expression of Wnt5a protein was also increased [42–44]. It has been reported that the Wnt/β-catenin signaling pathway can suppress IL-1β-induced cartilage degradation and inflammatory responses in chondrocytes [45] and downregulate expression of the RUNX2 gene to induce chondrocyte hypertrophy [46]. PRP-Exos-mediated activation of the canonical Wnt/β-catenin signaling pathway needs to be verified.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of Wnt5a protein was also increased [42–44]. It has been reported that the Wnt/β-catenin signaling pathway can suppress IL-1β-induced cartilage degradation and inflammatory responses in chondrocytes [45] and downregulate expression of the RUNX2 gene to induce chondrocyte hypertrophy [46]. PRP-Exos-mediated activation of the canonical Wnt/β-catenin signaling pathway needs to be verified.…”
Section: Introductionmentioning
confidence: 99%
“…43 There is large volume of evidence that indicates that fructose-overload activates the Akt/FOXO-1/SREBP1c signaling cascade, and that of hypoxia and inflammation (HIF-1α, VEGF, TNF-α) leading to the pathogenesis of insulin-resistant state. [44][45][46] As these are well-established treatment targets, we report here that, in pubescent rats with ad libitum access to fructose (15%), PG-HM acts as an insulin sensitizer by 1) incrementing signals of energy homeostasis (Akt, p-tyr-STAT -3 and SREBP-1C), 2) mitigating signals of de novo lipogenesis (AMPK alpha1), and hypoxia-inflammation (HIF-1α, VEGF, TNF-α). The PG-HM nullified the fundamental mechanisms involved in glucose intolerance and insulin The effect of PG-HM on molecular markers of hepatic metabolism was confirmed using the immortal, nontumorigenic, human hepatoma cells, HepG2, which were cultured in a fructose-rich environment (1mM), such that the FC2 simulated the hepatic insulin-resistant state with activated mTOR/ p-tyr-STAT-3 and HIF-1α, VEGF and TNF-α signaling pathways.…”
Section: Discussionmentioning
confidence: 83%
“…VEGF, one of the most important inducers of angiogenesis and vascular permeability, also has a strong link with inflammation and immunity [ 23 , 24 ] and can greatly change the tissue microenvironment and induce inflammation. [ 25 , 26 ] Contrary to the sharp rise in VEGF levels in APAC eyes, VEGF remained at a slightly higher level in the CACG eyes, indicating a hypoxic microenvironment in the anterior segment tissues of the CACG and the APAC eyes. It has been postulated that VEGF expression correlate with glaucoma aggressiveness and refractory treatment.…”
Section: Discussionmentioning
confidence: 88%